ANALISIS MINIMALISASI BIAYA PENGGUNAAN OBAT ANTIDIABETIK PASIEN RAWAT INAP DIABETES MELITUS DENGAN HIPERTENSI DI RUMAH SAKIT PKU MUHAMMADIYAH GAMPING PERIODE JANUARI-JULI 2024 - Nafiatul Khusna; Fatimah , Fitri Andriani; Listiana Hidayati; Melia Eka Rosita (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
Diabetes mellitus is a chronic disease with increasing prevalence globally. The prevalence of diabetes mellitus in the Special Region of Yogyakarta was 23.3% in 2022 and increased to 64.8% in 2023, with 17,050 sufferers in Sleman Regency. This high prevalence increases the risk of cardiovascular complications and increases the cost of treatment, which adds to the overall economic burden. The purpose of this study was to determine the characteristics of respondents, the profile of antidiabetic drugs, and the minimum cost of antidiabetic therapy for inpatients with diabetes mellitus and hypertension at PKU Muhammadiyah Gamping Hospital. The study was conducted using a descriptive design with retrospective secondary data collection from the medical records section for the period January-July 2024. Cost data were analyzed using the Cost Minimization Analysis (CMA) method. The results showed that the majority of patients were women aged 55–65 years with BPJS coverage. The most common single therapy was insulin novorapid flexpen (8 patients), while the most common combination therapy was metformin and novorapid flexpen (4 patients). The minimum therapy cost is Rp. 3,286,700 with the combination therapy group of insulin lantus and novorapid.